THE INFLUENCE OF GASOLINE’S AROMATIC CONTENT ON ENGINE COMBUSTION CHAMBER DEPOSIT FORMING - Djainuddin Semar; Nur Ahadiat (Scientific Contributions Oil and Gas, 2007)
Aromatic content in gasoline fuels should be limited due to its influencies to the cleanessof engine combustion chamber and emission of carbon monoxide, carbon dioxide andhidrocarbon. Ussually the highest aromatic content mean more higher its benzene contentand it will couse increase of air pullotion. According to specification of gasoline 91(SKNo. 3674 k/24/DJM/2006), maximum aromatic content is 50 % volume. Those specificationconform to catagory 1 of World Wide Fuel Charter (WWFC). However, aromatic and benzenecontent test on domestic gasoline in Indonesia obviously fulfil maximum limit for gasolinecatagory 2 of WWCF. Effect of several volume variaties of aromatic content in gasoline91 againts deposit development and cleaness (rating) of engine combution chamberwill be discuss in this paper.